Extraction and Photometric Studies of Fe-Cyanex 923 Complex - Mathias, Elton; Raman, Bhanu; Vaidya, S.P. (Asian Journal of Chemistry, 2010)
A detailed study of extraction of iron was carried out using Cyanex 923 in chloroform as an extractant. The Fe(III) content in the extracted colourless complex can be estimated using direct spectrophotometric method. Various parameters for extraction of iron were studied viz., HCl study, effect of reagent concentration, effect of various diluents and equilibration period. These conditions were optimized to obtain the quantitative extraction. The probable nature of the extracted species was found out by a plot of log D vs. log C. The interference of foreign ions on extraction of Fe(III) was studied. The method can be used to separate Fe(III) from Mn(II), Ni(II), Co(II) and Mg(II) in their binary mixtures. Analysis of Fe(III) in ores, alloys and pharmaceutical products have been performed successfully and are in good agreement with certified values.